2010
DOI: 10.1016/j.jvir.2009.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Shear Stress, Protein Expression, and Vessel Area in an Animal Model of Arterial Dilatation in Hemodialysis Grafts

Abstract: Purpose To evaluate the wall shear stress, protein expression of matrix metalloproteinases-2 (MMP-2), -9 (MMP-9), and the inhibitors (tissue inhibitor of matrix metalloproteinases-1 (TIMP-1), and -2 (TIMP-2)), and vessel area over time in a porcine model for hemodialysis polytetrafluoroethylene (PTFE) grafts. Materials and methods In 21 pigs, subtotal renal infarction was performed and 28 days later, a PTFE graft was placed to connect the carotid artery to the ipsilateral jugular vein. Phase contrast MR was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
(68 reference statements)
1
15
1
Order By: Relevance
“…Similarly, in carotid artery ligation model in mice, MMP-2 expression apparently increased at day 7 and proceeds to increase even 4weeks after vascular injury (9). This evidences show that MMP-2 and MMP-9 have different expression patterns in at different time points (27). But, in our study we demonstrated that MMP-2 and MMP-9 expressions appear to be similar at day 28 after vascular injury in rabbit model of carotid anastomosis.…”
Section: Discussionsupporting
confidence: 65%
“…Similarly, in carotid artery ligation model in mice, MMP-2 expression apparently increased at day 7 and proceeds to increase even 4weeks after vascular injury (9). This evidences show that MMP-2 and MMP-9 have different expression patterns in at different time points (27). But, in our study we demonstrated that MMP-2 and MMP-9 expressions appear to be similar at day 28 after vascular injury in rabbit model of carotid anastomosis.…”
Section: Discussionsupporting
confidence: 65%
“…[100, 109] MMP-2 and MMP-9, referred to as gelatinases due to their ability to break down gelatin and several other collagens in particular the type IV collagen of the basement membrane, are upregulated within as little as 3 hours after venous implantation. [43, 111-113] Ultrastructural studies have documented progressive loss of type IV collagen in the early bypass graft indicating destruction of basement membrane (BM) which normally surrounds 95% of saphenous vein medial SMCs. [114, 115] The SMC BM not only represents a physical barrier to SMC migration but focal contacts between SMC and BM laminin keeps the cell in a quiescent, differentiated phenotype.…”
Section: Molecular Remodelingmentioning
confidence: 99%
“…Many different remnant kidney animal models have been used to study the mechanism of chronic kidney disease (17-24). We used the murine model of chronic kidney disease to determine the changes in several important profibrotic genes.…”
Section: Discussionmentioning
confidence: 99%
“…Many different animals have been used for this model including rats, mice, rabbits, cats, dogs, baboons, and pigs (17-24). The purpose of the current report was to determine the expression pattern of a disintegrin and metalloproteinase with thrombospondin motif-1 (ADAMTS-1), MMP-2, MMP-9, and its inhibitors along with fibroblast specific protein-1 (FSP-1) in a murine remnant kidney model.…”
Section: Introductionmentioning
confidence: 99%